Prognostic Significance of C-reactive protein Vs Neutrophil Lymphocyte Ratio in Patients with Acute Myocardial Infarction in a Tertiary Care Hospital - Dr Bhaskara V Krishna Harsha; Dr Uma M A; Dr Kandula Venkata Sai Raghavendra, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Prior studies have independently researched the prognostic significance of CRP and NLR in the context of AMI, the comparative effectiveness of these biomarkers and their alignment with in-hospital outcomes remain largely unexplored territories. This study aimed to study the prognostic significance of C - reactive protein versus Neutrophil to Lymphocyte Ratio and their correlation with in-hospital outcomes in patients with AMI. Methods: A prospective observational study was conducted in patients admitted to the Cardiac Care Unit from October 2022 to July 2024. Study participants include Patients diagnosed with AMI admitted to the Cardiac Care Unit. 105 patients were included n the study. Blood samples were drawn at admission, on day 3 of admission, and sent for C-reactive protein levels, complete blood count. Complete blood counts were used to calculate the neutrophil-lymphocyte ratio. Patients were followed up during their hospital stay for in-hospital outcomes. Results: Of total, 60% (n=63) belonged to age group of 51-70 years, 75.2% (n=79) were males. The mean (SD) CRP level among patients with hospital stay ≤7 days was 25.1 (39.5) mg/dL and in 8-14 days it was 42.4 (57.5). The mean (SD) CRP level among patients who succumbed to illness was 130.9 (119.2) mg/dL and who recovered was 22.4 (20.1). The mean (SD) NLR level among patients with hospital stay ≤7 days was 4.6 (3.3) and in 8-14 days it was 4.9 (2.5). The mean (SD) NLR level among patients with cardiogenic shock was 5.4 (3.1) and without cardiogenic shock was 4.6 (3.1). The mean (SD) NLR level among patients who succumbed to illness was 6.9 (3.3) and who recovered was 4.6 (3.0). Conclusion: The study demonstrates the significance of inflammatory markers, particularly CRP, as predictors of adverse outcomes in patients with AMI. Elevated CRP levels on the first- and third-days following AMI were associated with longer hospital stays, cardiogenic shock, and mortality. These findings suggest that CRP could serve as a valuable prognostic indicator for identifying patients at higher risk of complications post-AMI.